A proposal of seismic oceanography for temperature model inversion of the East Sea, Korea - Ha, Jiho; Shin, Sungryul; Chung, Wookeen; Choi, Yeonjin; Hong, Boram; Koo, Namhyung (Geosystem engineering, 2015)
Much attention has recently been paid to the East Sea because of the great influence it exerts on weather in the Korean peninsula as well as its peculiar oceanographic features. A large number of oceanographic observations have been made to probe the physical properties of the waters at the East Sea. However, until now, measuring the physical properties of a broad oceanic area simultaneously was impractical. To address this problem, this study presents a methodology to measure the physical properties of seawater by introducing seismic oceanography (SO) into marine seismic surveys. SO has been attracting attention as a new technology capable of concurrent analysis of a broad oceanic area; however, hardly any research of this type has been conducted in Korea to date. The technique proposed in this study involves derivation of a seawater temperature model based on the 1D seismic waveform inversion and Leroy equations using seismic data and non-stationary ARGO data. The proposed technique was validated through numerical model experiments using the seawater temperature information obtained at the East Sea in 2013, through which much insight into the ocean currents and seawater characteristics of the East Sea could be gained.